Dual regulation of osteoclastogenesis and osteogenesis for osteoporosis therapy by iron oxide hydroxyapatite core/shell nanocomposites. Issue 5 (23rd August 2021) - Li, Mengye; Fu, Shengxiang; Cai, Zhongyuan; Li, Danyang; Liu, Li; Deng, Di; Jin, Rongrong; Ai, Hua
Abstract: Osteoporosis is a skeletal disorder resulted in significant structural and functional changes, arousing a wide concern for the high prevalence and cost. Imbalance between osteoclastogenesis and osteogenesis have been verified as a main pathology etiology and considered an efficient therapy target in both clinical and pre-clinical studies. In recent years, inorganic nanomaterials have shown provable activities on osteoclastogenesis inhibition and osteogenesis promotion, respectively. Hence, in this study, a class of hydroxyapatite coated superparamagnetic iron oxide nanoparticles (SPIO@HA) were developed with a core−shell structure for targeting both osteoclastogenesis and osteogenesis. The optimal ratio of SPIO@15HA (Fe/Ca = 1:15, mol/mol) was screened to obtain dual function for inducing both bone formation and preventing bone resorption. The obtained nanocomposites significantly prevented the bone loss of ovariectomized (OVX) mice and increased bone mineral density (BMD) by 9.4%, exhibiting high bone accumulation in magnetic resonance imaging evaluation and reasonable biosafety profile. The mechanism study revealed that SPIO@15HA can suppress bone marrow monocyte derived osteoclast differentiation through TRAF6−p62−CYLD signaling complex regulation. Meanwhile, it could activate MSC osteogenic differentiation by TGF-β, PI3K-AKT and calcium signaling pathway regulation. Moreover, incubation of SPIO@15HA with MSC resulted in several cytokines overexpression such as osteoprotegerin (OPG), CSF2, CCL2 etc., which are responsible for maintaining the bone remodeling balance. The dual function of as-prepared SPIO@15HA may find a new way for designing of inorganic components containing core/shell nanomaterials for osteoporosis treatment.